Planning the 4-H Club Program - John A. Rutledge; Joy Cantrell Jordan (EDIS, 2003)
Good 4-H club programs don’t just happen. A lot of planning comes first. A 4-H club program plan serves as a road map of the club’s activities, helping to guide the club toward its goals. This publication was originally created by John A. Rutledge, Jr., August, 1985 and was revised by Joy C. Jordan, August, 2002.